2008
DOI: 10.1007/s10096-008-0659-3
|View full text |Cite
|
Sign up to set email alerts
|

Variable number tandem repeat loci providing discrimination within widespread genotypes of Acinetobacter baumannii

Abstract: Some genotypes of Acinetobacter baumannii, defined by pulsed-field gel electrophoresis (PFGE), have been found in many hospitals. Our aim was to find variable number tandem repeat (VNTR) loci capable of providing discrimination among isolates with highly similar or identical PFGE profiles, to gain insights into the epidemiology. Thirteen loci identified in A. baumannii ATCC 17978 were tested using a panel of isolates that included multiple representatives of genotypes belonging to the three European clonal lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…In contrast, multiple-locus variable-number tandem-repeat (VNTR) analysis (MLVA), based on the copy numbers of tandem-repeat units (TRs) of VNTR loci, is a highly reproducible and portable typing method and can be easily shared. So far, 10 VNTRs that provided sufficient repeat polymorphism for fine typing of clinical isolates have been described in A. baumannii, and three different selections of loci have been evaluated, including a 2-locus assay (9), an MLVA-8 scheme (10), and a partially automated MLVA-10 Orsay scheme (11).…”
mentioning
confidence: 99%
“…In contrast, multiple-locus variable-number tandem-repeat (VNTR) analysis (MLVA), based on the copy numbers of tandem-repeat units (TRs) of VNTR loci, is a highly reproducible and portable typing method and can be easily shared. So far, 10 VNTRs that provided sufficient repeat polymorphism for fine typing of clinical isolates have been described in A. baumannii, and three different selections of loci have been evaluated, including a 2-locus assay (9), an MLVA-8 scheme (10), and a partially automated MLVA-10 Orsay scheme (11).…”
mentioning
confidence: 99%
“…For example, the predominant PFGE type from United Kingdom hospitals, known as OXA-23 clone 1, a sublineage of international clone II, has been found in over 60 hospitals. We have successfully used variable-number tandem repeat (VNTR) analysis at two highly discriminatory loci to provide fine typing within a PFGE cluster, which does appear to reflect the known epidemiology (29). However, the finding of genetically similar isolates in multiple locations, sometimes with no known epidemiological link, raises questions about the relative roles of spread and selection by antibiotics, and it would be helpful to compare these isolates in more detail.…”
mentioning
confidence: 99%
“…VNTR have been found in the genomes of several bacteria including Staphylococcus aureus, Bacillus anthracis, Bacillus cereus and Neisseria 7,8,9,10,11 . Turton et al 12 and Pourcel et al 6 suggested the use of VNTR as a complement or even for substitution of the other methodologies. VNTR is a technique based on the PCR detection of specific repetitive sequence(s) active in different individuals, which results in an electrophoretic fingerprint.…”
mentioning
confidence: 99%
“…VNTR is a technique based on the PCR detection of specific repetitive sequence(s) active in different individuals, which results in an electrophoretic fingerprint. Multiple-locus VNTR analysis, also known as MLVA, presents the polymorphism among different tandemly repeated DNA sequences 12 . The division of VNTR markers into two groups is made according to their size and rate of evolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation